Is Male Androphilia a Context-Dependent Cross-Cultural Universal? - Hames, Raymond; Garfield, Zachary; Garfield, Melissa (Archives of Sexual Behavior, 2017)
The cross-cultural ethnographic literature has traditionally used the label male "homosexuality" to describe sexual relationships between biological males without considering whether or not the concept encompasses primary sexual attraction to adult males. Although male androphilia seems to be found in all national populations, its universal existence in tribal populations has been questioned. Our goal is to review previous cross-cultural classifications and surveys of male same sex behavior to present a system that does justice to its varied expressions, especially as it is informed by contemporary sexuality research. Previous comparative research does not effectively distinguish male same sex behavior from male androphilia. Using the standard cross-cultural sample (SCCS) as a sampling frame and the ethnographic sources in the human relations area files and elsewhere, we present distributional data on various forms of male same sex behavior. The SCCS is useful because it is designed to be representative of all historically known social formations and the sample is designed to reduce similarities as a consequence of common descent or historical origin as well as reduce the probability of diffusion of sociocultural practices from one culture to another. Our results show that male same sex behavior as well as male androphilia is much more common than previously estimated in the SCCS. With our findings, we make an argument that male androphilia is a context-dependent cross-cultural universal.